Searching for orbits to observe Iapetus - Ferreira, Lucas S. [UNESP]; Prado, Antônio F. B. A.; Sfair, Rafael [UNESP] (Springer Nature, 2023)
It is in the interest of astronomy and engineering to find orbits for spacecraft that allow a good observation of the orbited body and, at the same time, to reduce expenses with fuel consumption for correction and maintenance maneuvers. Considering the current scenario, many of the small bodies in the Solar System have been shown to be good candidates for future study missions, such as planetary moons, asteroids, and dwarf planets, beyond the orbit of Neptune. In this sense, the search for methods that aim to locate favorable orbital configurations for the placement of a spacecraft is an important point to be studied. In particular, it is important to search for orbits with high inclinations and circular or quasi-circular, since these orbits allow the observation of the entire body during its natural rotation. However, these orbits are subject to strong perturbations due to the presence of effects, such as those caused by mother planets and the inhomogeneity of the mass and the shape of the satellites. So, the goal of the present paper is to search for orbital configurations for a spacecraft around small satellites. Therefore, in this paper, we study the perturbations given by planet Saturn in a spacecraft orbiting the satellite Iapetus.